The islamic ethics and the radical reform : an analysis of Tariq Ramadan's view - Abdus Salam, Yunus Olatoke
The study of re-thinking Islam or the reformulation of Islam has become one of the most researched areas nowadays. There are many available pieces of literature in the field of reform in Islam but literature on ÙÉriq RamaÌÉn's major works known as Radical Reform: Islamic Ethics and Liberation, are so few and superficial. Hence, the present study aims at contributing to the few available writings on the subject and to fill the gaps wherever relevant. In the former perspective, the thesis tries to locate the Islamic ethics as it could be found in the Qur'Én, the Sunnah and other sources of Islamic heritage with special focus on ÙÉriq RamaÌÉn's major work known as Radical Reform: Islamic Ethics and Liberation, which contains very significant ideas and observations on the subject matter and which is considered solution to the contemporary challenges facing Muslims in the world over. The objective of the research besides understanding the nature of Islamic ethics and radical reform is to propose a framework of Islamic ethics that can be used to develop the conditions of the Ummah in order to find possible solution to the challenges that confront the contemporary Muslim societies. In an attempt to carry out this task, descriptive, analytical, and critical methods were used. The finding shows that comprehensive understanding of the texts first and then context based on our own criteria of observation, experience, analysis and examination is needed to solve the contemporary challenges faced by Muslims over the world. The fresh study of the existing happenings or conditions of life and society is necessary. The process of Islamization of modern Knowledge and Disciplines is highly required not to assign a due place to the full understanding and adequate knowledge of all fields of human endeavors. In addition to this, any priority cannot be given to the context without having the full understanding and knowledge of the texts. It is the texts which guide Muslims to study and understand properly the context.